2018
DOI: 10.1107/s205698901800974x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure, DFT studies and UV–Vis absorption of two new linear fused ring chalcones: (E)-1-(anthracen-9-yl)-3-(2-methoxyphenyl)prop-2-en-1-one and (E)-1-(anthracen-9-yl)-3-(3-fluoro-4-methoxyphenyl)prop-2-en-1-one

Abstract: The title compounds were synthesized using the Claisen–Schmidt condensation method and characterized by UV–Vis spectroscopy. The geometrical parameters optimized using density functional theory (DFT) calculations show a good correlation with the experimental results. The small HOMO–LUMO energy gaps of 3.11 and 3.07 eV enhances the non-linear responses of these mol­ecular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The stronger absorption at 275–295 nm belonged to the π-π* transition and indicated that there was a phenolic constitute or nucleic acid in the samples [ 16 ]. The stronger absorption at 310–330 nm can be assigned to the n-π* transition or the electron delocalization due to the C–O–C coupling [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The stronger absorption at 275–295 nm belonged to the π-π* transition and indicated that there was a phenolic constitute or nucleic acid in the samples [ 16 ]. The stronger absorption at 310–330 nm can be assigned to the n-π* transition or the electron delocalization due to the C–O–C coupling [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1b exists in the stereoselective s-trans conformation with respect to the C8=C9 [1.324(2) Å] and C7=O7 [1.217(18) Å] double bonds. Apparently, this conformation is the predominant form in crystallized chalcone derivatives molecules with low planarity[39][40][41][42].…”
mentioning
confidence: 94%